Italian Adaptation and Psychometric Properties of the Prejudice Against Immigrants Scale (PAIS): Assessment of Validity, Reliability, and Measure Invariance - Salvati, Marco; Basili, Emanuele; Carone, Nicola; Giacomantonio, Mauro (Frontiers in Psychology, 2020)
The aim of the current study was to adapt and validate the Prejudice Against Immigrants Scale (PAIS) in the Italian context, based on the Prejudice Against Asylum Seekers Scale (PAAS) by Anderson (2018). The validity, reliability, and measurement invariance across gender, age, and educational levels of the scale were assessed through three sources which involved 306 Italian individuals (NMen = 151, 49.3%) between 18 and 60 years. Both Exploratory (EFA) and Confirmatory factor analyses (CFA) confirmed the two-factor solution of the original instrument by excluding two items which were present in the previous validation study. The first factor is classical prejudice against immigrants (PAIS-CL) which maps onto theoretical derivations of classical and old-fashioned prejudices, whereas the second factor is conditional prejudice against immigrants (PAIS-CO) which maps onto theoretical derivations of subtle and modern prejudices. Findings of the multigroup CFAs demonstrated full configural and metric invariance, and partial scalar invariance of the scale across gender, age and educational level. The analyses confirmed that PAIS has high levels of reliability, and criterion, and construct validity, showing findings which are comparable to those of Anderson (2018). These results suggest that PAIS presents very good psychometric properties and could be considered a valid and reliable instrument to measure prejudice against immigrants, by enabling Italian researchers to detect both covert and more subtle forms of prejudice against immigrants. Limitations and further directions are discussed.